Design and experimental implementation of an effective control system for thin film Cu(InGa)Se2 production via rapid thermal processing. (October 2016) - Lovelett, Robert J.; Hanket, Gregory M.; Shafarman, William N.; Birkmire, Robert W.; Ogunnaike, Babatunde A.
Highlights: We design and operate a pilot-scale rapid thermal processing (RTP) reactor to produce Cu(InGa)Se2 thin films. We develop thermal models to describe temperature evolution in the physical system. We design and experimentally implement an observer and a controller that track temperature ramp set points effectively in the RTP reactor. Abstract: Copper indium gallium diselenide, Cu(InGa)Se2 (CIGS) solar cells have achieved efficiencies of 22.3% at the cell level and 17.5% at the module level. CIGS-based modules are also in the early stages of commercialization, with >1 GW annual production capacity. The most common method for producing CIGS in industry is via precursor reaction, which consists of depositing Cu-In-Ga precursor films and reacting them with gas-phase H2 Se at 450–550 °C for 60 min or longer, and is commonly called selenization. Recently, interest has been growing in selenization by Rapid Thermal Processing (RTP), which is characterized by rapid temperature ramping, approximately 550 °C or higher temperature reactions, and improved process throughput. However, it has been difficult to commercialize RTP for CIGS film production in part because implementing a rapid, linear temperature ramp in the reacting thin film is complicated by two intrinsic process characteristics: (i) the temperature of the CIGS film cannot usually be measured directly; and (ii), the process is significantly nonlinear due to the dominance of radiative heat transfer at high temperatures. In this paper, we present the design and modeling, construction, and successful operation of a pilot-scale RTP selenization reactor utilizing a novel temperature control system. Our two-fold approach to the unique temperature control challenges involves the design and implementation of (i) a first-principles, model-based observer to estimate the desired surface temperature; and (ii) a specialized controller to enable effective tracking of the desired linear temperature ramp set point. Our experimental results demonstrate that the control system is effective in tracking rapid temperature ramps accurately, with performance limited only by the physical constraints of the experimental system.